How variance affects a project’s timeframe and costs. - Izar Landeta, Juan Manuel; Villalón Piña, Olga Edith; Ruiz Aguilar, Javier (HITOS DE CIENCIAS ECONÓMICO ADMINISTRATIVAS, 2026)
OBJECTIVE: To study the application of several methods to estimate the timeframe of a project, in order to analyze the correlation between the variance of the project and the completion of the timeframe and penalty costs.MATERIAL AND METHOD: Several methods were applied to estimate the timeframe and the variance of the project, starting with PERT and continuing with other methods derived from PERT, along the triangular distribution, the Ballesteros-Pérez et al., and the Montecarlo simulation.RESULTS: The methods were applied to an illustrative project case. The methods of Suckey and Kim, Shankar and Sireesha, Golenko-Ginzburg, and Grubbs yielded the shortest project completion times and the lowest penalty costs for delays. PERT achieved an intermediate position, indicating that it is not the best solution.CONCLUSIONS: It is confirmed that variance does have a direct relationship with both the project timeline and its costs in the case of delays. PERT has been placed in an intermediate position both in terms of project timeline and penalty costs for delays.
Keywords: project timeframe; critical path; expected activity time; activity variance; beta probability distribution.